Gene expression profiling in necrotizing enterocolitis reveals pathways common to those reported in Crohn's disease. Issue 1 (December 2015) - Tremblay, Éric; Thibault, Marie-Pier; Ferretti, Emanuela; Babakissa, Corentin; Bertelle, Valérie; Bettolli, Marcos; Burghardt, Karolina; Colombani, Jean-François; Grynspan, David; Levy, Emile; Lu, Peng; Mayer, Sandeep; et al.
Abstract Background Necrotizing enterocolitis (NEC) is the most frequent life-threatening gastrointestinal disease experienced by premature infants in neonatal intensive care units. The challenge for neonatologists is to detect early clinical manifestations of NEC. One strategy would be to identify specific markers that could be used as early diagnostic tools to identify preterm infants most at risk of developing NEC or in the event of a diagnostic dilemma of suspected disease. As a first step in this direction, we sought to determine the specific gene expression profile of NEC. Methods Deep sequencing (RNA-Seq) was used to establish the gene expression profiles in ileal samples obtained from preterm infants diagnosed with NEC and non-NEC conditions. Data were analyzed with Ingenuity Pathway Analysis and ToppCluster softwares. Results Data analysis indicated that the most significant functional pathways over-represented in NEC neonates were associated with immune functions, such as altered T and B cell signaling, B cell development, and the role of pattern recognition receptors for bacteria and viruses. Among the genes that were strongly modulated in neonates with NEC, we observed a significant degree of similarity when compared with those reported in Crohn's disease, a chronic inflammatory bowel disease. Conclusions Gene expression profile analysis revealed a predominantly altered immune response in the intestine of NEC neonates. Moreover, comparative analysis between NEC and Crohn's disease gene expression repertoires revealed a surprisingly high degree of similarity between these two conditions suggesting a new avenue for identifying NEC biomarkers.